Diasporas and ethnic migrants : Germany, Israel, and post-Soviet successor states in comparative perspective - Münz, Rainer, 1954-; Ohliger, Rainer, 1967- (Cass series--nationalism and ethnicity., 2003)
This work adopts a comparative approach to explore interrelations between two phenomena which, so far, have rarely been examined and analysed together, namely the dynamics of diaspora and minority formation in Central and Eastern Europe on the one hand, and the diaspora migration on the other.